Modern priorities of ensuring foreign economic security of Georgia - Veshapidze, Shota (Ivane Javakhishvili Tbilisi State University Paata Gugushvili Institute of Economics, 2023)
Economic security is one of the most important features of the economy, and ensuring the safe functioning of the country's economy is a necessary condition for its competitive and sustainable development. It is important to systematize conceptual approaches to ensuring external economic security in the context of global risks and threats. Basic approaches to the concept of economic security of the country and methods of fighting it are defined by different concepts. Among them, the institutional concepts of protection against cameralist, Keynesian and administrative barriers are noteworthy. Foreign competitors (according to F. Liszt), "market failure" (according to J. M. Keynes) and "state failure" (according to H. De Soto) can pose threats to the economic security of each country. Different strands of foreign trade policy are important, including mercantilism, protectionism, free trade, super-protectionism, private monopoly protectionism, collective protectionism, and neo-protectionism. Depending on the different motives for the introduction of trade barriers, five types of neo-protectionism can be distinguished: "protectionism of lobbyists," "protectionism of industrialists," "protectionism of geostrategists," "protectionism of populists," "benevolent protectionism." The main role in the intensive growth of trade barriers belongs to developed countries, which previously supported free trade and globalization They were catchers. External economic security is ensuring the development of economic processes in the country, which will create the necessary (acceptable) conditions and resources for economic stability and development of society. The national security of the country is characterized, first of all, by the state of the economy and its competitiveness on the world markets. The more stable and competitive the economy, the higher its level of economic security. Foreign economic security includes its provision in the main forms of international economic relations, such as: problems of ensuring economic security within the international division of labor; Assessment of the results of direct and portfolio investments in the global economy for the external economic security of the country; ensuring foreign economic security of international trade; Modern monetary and financial system and international economic security. There is a close relationship between modern technologies, economic security and the growth of sustainable economic development potential in Georgia. The influence of the fourth industrial revolution on the economic and innovative potential of Georgia is decisive. Technological progress helps increase economic opportunity and prosperity. The role of innovative policy in ensuring the economic security of the state is great. Successfully solving the problems of attracting investments in the field of science is an important factor in the growth of natural, industrial, scientific, technical and labor potential of Georgia. The emergence of the Internet, the development of artificial intelligence, blockchain, Internet of Things and 5G technologies has accelerated the digital transformation of the world economy. The rapid development of digital technologies has created a highly coordinated digital economy that transcends geographic boundaries and industry sectors. Digital transformation in the global economy brings both positive results and threats to its development. Significant economic benefits resulting from the digitization of the economy include increased productivity, job creation, enhanced international trade and innovation. In addition, there are potential risks and negative effects. The workplace is being replaced by technology, data privacy is at risk, market issues and etc. The official documents received by the Georgian state allow for the regulation and maintenance of the country's security management processes. At the same time, the modern mechanism of ensuring economic security must be constantly transformed along with new risks and threats emerging in the country's economic sector. Correct positioning to overcome external and internal threats to the national economy ensures the economic sovereignty of the country, the unity of its economic space and the conditions for the implementation of strategic national priorities. Practical importance It is important to identify the existing threats to the external economic security of the Republic of Georgia and to develop directions for improving the security system, which ensures a favorable international position of the national economy. This means not identifying the importance of one type of threat in relation to others, but studying their interrelationship, interdependence and mutual influence. To build an effective system of external economic security, it is necessary to identify the most dangerous external threats, to rank them in order to determine the directions that require operational regulation or consistent strategic neutralization. When assessing threats, it is necessary to use both the entire complex system of indicators, as well as their threshold values, which reflect the boundaries of safe development of the national economy. This will make it possible to identify Georgia's external economic threats, challenges and risks, develop tools and recommendations for its solution. The formation of the national security strategy of Georgia can be determined according to a 5-step system scheme, which includes: Determination of the theoretical concepts, methodological sources and basic concepts of the strategy; Assessment of Georgia's involvement in today's world based on the analysis of the current situation: trends and opportunities; National interests and national strategic priorities of Georgia; Ensuring national security; Strategy realization organization and mechanisms.
1. აბესაძე რ. (2020). საქართველოს ინოვაციური პოლიტიკა და სისტემა. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XIII. თბილისი, გვ.10–46. ელექრონული რესურსი: https://www.pgie.tsu.ge/contentimage/xxxx/shr.kreb.2020.pdf 2. აბესაძე რ. (2022). საქართველოს ეკონომიკური უსაფრთხოების სტრატეგიის შემუშავების ძირითადი თეორიულ-მეთოდოლოგიური პრობლემები. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.9–27. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 3. ასლამაზიშვილი ნ. (2003). საგარეო ვაჭრობა. თბილისის უნივერსიტეტის გამომცემლობა, თბილისი. 4. ბასილია თ., სილაგაძე ა., ჩიკვაიძე თ. (2001). პოსტსოციალისტური ტრანსფორმაცია: საქართველოს ეკონომიკა XXI საუკუნის მიჯნაზე. თბილისი. 5. ბედიანაშვილი გ. (2023). პოსტპანდემიური პერიოდის მაკროსისტემური სოციალურ-ეკონომიკური გამოწვევები. ეროვნული სამეცნიერო კონფერენციის მასალები: “მსოფლიო ეკონომიკა პოსტპანდემიურ პერიოდში: შედეგები და გამოწვევები“. ივანე ჯავახიშვილის სახელობის თბილისის სახელმწიფო უნივერსიტეტი, ეკონომიკისა და ბიზნესის ფაკულტეტი. 41- 46. 6. ბედიანაშვილი გ. (2018). კულტურა როგორც ცოდნის ეკონომიკის ფორმირების ფაქტორი პარადიგმული ცვლილებების სისტემურ-ინსტიტუციური კონტექსტით. გლობალიზაცია და ბიზნესი. 6, 58-66. DOI: 10.35945/gb.2018.06.007 7. ბერულავა გ., ცუცქირიძე მ. (2022). ეკონომიკური უსაფრთხოების და ეკონომიკური მდგრადობის თეორიულ-მეთოდოლოგიური ასპექტები: საერთაშორისო გამოცდილება. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.114–129. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 8. ბურდული ვ. (2022). გლობალური ეკონომიკური საფრთხეები და მათი გავლენა ეროვნულ ეკონომიკურ უსაფრთხოებაზე. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.55–113. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 9. ვეშაპიძე შ. (2018). კაცობრიული ღირებულებები ეკონომიკური ხედვით. თბილისი, „SMARTY.” 10. კეინსი ჯ. (1995). დასაქმების, პროცენტისა და ფულის ზოგადი თეორია / თარგმნა რამაზ ნამიჭეიშვილმა; [რედ.: ელგუჯა თავბერიძე]. ქუთაისი : ს/ს "სტამბა" 11. კვარაცხელია მ. (2022). გლობალიზაცია და ეკონომიკური უსაფრთხოების პრობლემები საქართველოში. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.130–144. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 12. თოდუა გ. (1996). მდგრადი ეკონომიკისა და შეფარდებითი უპირატესობის ერთიანობის საყოველთაო კანონი. ჟურნალი „ეკონომიკა,“ N 12, გვ. 28–32. 13. ლაზარაშვილი თ., კაკულია ე. (2022). გლობალური სოციალური საფრთხეები და მათი ეროვნულ სოციალურ უსაფრთხოებაზე გავლენის თეორიული საკითხები. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.155–171. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 14. მაჩაიძე რ. (2023). უკრაინის „ავღანეთიზაციის“ საფრთხე და საქართველოს ეკონომიკური გამოწვევები. 20 ივლისი.https://kvirispalitra.ge/article/105165ukrainis-avganetizaciis-saprtxe-da-sakartvelos-ekonomikuri-gamocvevebi/ 15. მექვაბიშვილი ე. (2018). გლობალიზაციის ეპოქის ფინანსური კრიზისები და საქართველოს ეკონომიკა. თბილისი, გამომცემლობა „ინტელექტი.“ 16. პაპავა ვ. (2022). დეგლობალიზაციის პრობლემა და განახლებული გლობალიზაციის პირობებში ეროვნული ეკონომიკური უსაფრთხოების ძირითადი გამოწვევები. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.28–54. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 17. ქისტაური, ნ; მელაშვილი, მ; ქველაძე, კ. (2018). ეკონომიკური უსაფრთხოება და მასზე მოქმედი ფაქტორები. თსუ პაატა გუგუშვილის სახელობის ეკონომიკის ინსტიტუტი ივანე ჯავახიშვილის სახელობის თბილისის სახელმწიფო უნივერსიტეტის 100 წლისთავისადმი მიძღვნილი საერთაშორისო სამეცნიერო ინტერნეტ-კონფერენცია. Web:https://www.researchgate.net/publication/330637847_ekonomikuri_usaprtkhoe ba_da_masze_mokmedi_paktorebi. ბოლო ნახვა: 30/05/2023. 18. ხუსკივაძე მ. (2022). ეკოლოგიური უსაფრთხოების სფეროში ევროკავშირის გამოცდილების განზოგადება. თსუ პაატა გუგუშვილის ეკონომიკის ინსტიტუტის სამეცნიერო შრომების კრებული. ტომი XV. თბილისი, გვ.222–238. ელექრონული რესურსი: http://pgie.tsu.ge/contentimage/xxxx/2022srkrydit.pdf 19. საქართველოს ადამიანის უფლებათა დაცვის ეროვნული სტრატეგია 2022- 2030 წლებისთვის. https://faolex.fao.org/docs/pdf/geo216923.pdf 20. საქართველოს ეროვნული უსაფრთხოების კონცეფცია. https://mfa.gov.ge/national-security-concept 21. საქართველოს კანონი ინფორმაციული უსაფრთხოების შესახებ. http://www.economy.ge/uploads/kanonmdebloba/kavshirgabmuloba/informaciuli _usafrtxoeba.pdf 22. საქართველოს კანონი „ეროვნული უსაფრთხოების პოლიტიკის დაგეგმვისა და კოორდინაციის წესის შესახებ.“ მიღების თარიღი: 23/03/2015. https://matsne.gov.ge/ka/document/view/2764463?publication=13 23. საქართველოს კანონი „ინფორმაციული უსაფრთხოების შესახებ. “საქართველოს საკანინმდებლო მაცნე. მიღების თარიღი: 05/06/2012. https://matsne.gov.ge/ka/document/view/1679424?publication=5 24. ხედვა 2030 საქართველოს განვითარების სტრატეგია. https://www.gov.ge/wpcontent/uploads/2022/11/khedva-2030-saqarthvelos-ganvitharebis-strategia-1.pdf 25. საქართველოს 2021-2030 წლების მიგრაციის სტრატეგია. https://migration.commission.ge/files/ms_2021-2030_geo.pdf 26. Bedianashvili G. (2023). Macrosystemic Challenges of Uncertainty under the Conditions of Confrontational Globalization. Bulletin of the Georgian National Academy of Sciences. 17(2), 174-179. 27. Gadzhiev N. G., Gazimagomedov M. A., Doronin A. V. (2021). Ekonomicheskaya bezopasnost [Economic security] (in Russian). 28. Gvelesiani, M., & Veshapidze, S. (2016a). European Values: What Can We Implement from Them and How Can We Implement Them in Georgia. Globalization & Business. (1). 40-46. (In Georgian). 29. Gvelesiani, M., & Veshapidze, S. (2016b). Values: Limits and Contradictions. Globalization & Business, (1). 35-39. (In Georgian). Otinashvili, R., Veshapidze, S., & Zoidze, G. (2021). IMPACT OF ECONOMIC CRIME ON THE SUSTAINABLE DEVELOPMENT OF THE STATE. Three Seas Economic Journal 4 (1), 10-17 31. Papava, V. (2018). The Economics in Crisis and the Main Directions for Transformation of Economic Science. Transformations, 3-4(98-99), 90-108 32. Papava, V. (2021). On Pseudo De-Globalization, Silk Road Of Global Value Chains And Role Of Georgia – OpEd. https://www.eurasiareview.com/18102021-on-pseudode-globalization-silk-road-of-global-value-chains-and-role-of-georgia-oped/. 33. Papava, V. (2022a). Pandemic, War and Economic Sanctions: From Turbulent to Confrontational Globalization. Eurasia Review, May 23, https://www.eurasiareview.com/23052022-pandemic-war-and-economicsanctions-from-turbulent-to-confrontational-globalization-oped/. 34. Papava, V. (2022b). On Sanctionomics. Eurasia Review, March 14. Available at: https://www.eurasiareview.com/14032022-on-sanctionomics-oped . 35. Silagadze, A., Atanelishvili, T., & Silagadze, N. (2022). Covid Depression and Search for a New Paradigm. Bull. Georg. Natl. Acad. Sci, 16(1). 36. Veshapidze, S., (2017). THE TRADITIONS ORIENTATED ON EUROPEAN VALUES IN GEORGIA. Sciences of Europe. VOL 4, No 13 (13) 37. Veshapidze, S. (2022). Ilia Chavchavadze on the Methodological Aspects of Economic Processes Research and Modernity. Conference: VII International Scientific Conference. At: Tbilisi, Georgia. 38. Veshapidze, S., & Karchava, L. (2022). Contradictions of Globalization under the COVID-19 Pandemic. Bull. Georg. Natl. Acad. Sci, 16(4). 39. Veshapidze, S., & Putkaradze, R. (2023). International economic relations of Georgia at the modern stage of globalization. “Ekonomisti” #1, 58–69. 40. Veshapidze, S., & Zoidze, G. (2021). Institutional Evolution of Higher Education in Georgia. The New Economist, 16(2), 1–1. DOI: https://doi. org/10.36962/NEC6102202133 41. Veshapidze, S., & Zoidze, G. (2022a). On State Intervention in the Economy through the Budget in Georgia. WORLD ECONOMY AND INTERNATIONAL ECONOMIC RELATIONS. - International Scientific Collection - Vol. 5. Kyiv – CUL. https://doi.org/10.5281/ zenodo.5807500 42. Veshapidze, S., & Zoidze, G. (2022b). Value Choices of the Community in the Context of the COVID-19 Pandemic. DOI: https://doi. org/10.5281/ zenodo, 6373197. 43. Veshapidze, S., Babuadze, N., & Beridze, T. (2015). EUROPEAN VALUES AND CHOICE OF GEORGIA (HUMAN DIGNITY, LAWFUL SOVEREIGNTY, DE- MOCRACY AND WELLBEING). ACTUAL PROBLEMS OF SUSTAINABLE DE- VELOPMENT OF NATIONAL ECONOMIES.(10-11 July, 2015). PUBLISHING HOUSE OF PAATA GUGUSHVILI INSTITUTE OF ECONOMICS OF IVANE JAVAKHISHVILI TBILISI STATE UNIVERSITY. Tbilisi, 79-83. 44. Veshapidze, S., Zubiashvili, T., & Chiabrishvili, K. (2021). Globalization and New Opportunities for Georgia. Globalization and Business. 12, 32-36. https://doi.org/10.35945/gb.2021.12.003 45. Veshapidze S., Otinashvili R., Gvarutsidze A., Abuselidze G., Zoidze G. (2022). Modern technologies to overcome the challenges of globalization. Entrepreneurship, 10 (2), 22-32 DOI: 10.37708/ep.swu.v10i2.2 46. Zoidze, G., & Veshapidze, S. (2022a). The Modern Economy and Values. Cambridge Scholars Publishing. P. 125; 47. Zoidze, G., & Veshapidze, S. (2022b). Transformation of Economic Policy Priorities Under Covid-19. Three Seas Economic Journal, 3(2), 35-43. 48. The Global Risks Report 2021. Weforum.org. [ელექტრონული რესურსი]. http:// www3.weforum.org/docs/WEF_The_Global_Risks_Report_2021.pdf (ბოლო ნახვა: 28.07.2023).